Exploring economic support networks amidst racial inequality in Namibia - Annalena Oppel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Community or interpersonal support as a critical source of livelihood sustenance in the Global South can exhibit unequal dynamics. An understanding of these practices is primarily tied to the conceptual space of poverty or small communities. Less is known about how social support systems might respond to structural inequalities. I address this by exploring how support practices might be shaped by inequalities in the Namibian context. I draw on primary network data to assess inequality as a social dynamic within the space of support and evaluate whether providing worseoff others corresponds to former discriminatory practices under the apartheid regime. My results suggest that inequality has normalized a sense of support as necessity for black but not white Namibians. More broadly, by recognizing differences in group practices, I evidence that exploring support practices across structural inequalities can enhance insights on the social replication of inter- and intragroup-based inequalities.
Keywords: C30; D10; D31; D63; 330; inequality; race; economic support; personal networks; Africa; Namibia